Ambroxol Inhibits Neutrophil Respiratory Burst Activated by Alpha Chain Integrin Adhesion. (October 2013) - Peroni, D.G.; Moser, S.; Gallo, G.; Pigozzi, R.; Tenero, L.; Zanoni, L.; Boner, A.L.; Piacentini, G.L.
The purpose of the present study was to investigate the possible anti-oxidant effect(s) of Ambroxol on neutrophils activated by ligand-binding of the drug with membrane-associated adhesion integrin CD11a and to estimate dose-response changes in oxygen free radical production. The amount of free radical production by anti-CD11a- and anti-CD4-coated neutrophils stimulated with N -formyl-methionylleucyl-phenylalanine (FMLP) and challenged with increasing concentration of Ambroxol, was evaluated within a time frame of 90 minutes. A significant dose-dependent effect response of Ambroxol on O2 − production by cells coated with anti-CD11a antibody was observed. This preliminary study opens a new perspective on the therapeutic role of Ambroxol as an antioxidant drug and for its potential use in controlling oxidative stress, particularly in leukocyte-dependent inflammation.